A succinyl isoflavone identified in natto promotes anti-ischemic effects in the middle cerebral artery occlusion rats. (October 2020) - Bao, Ke; Chen, Tian-Li; Zhang, Sen; Huang, Zi-Zheng; Huang, Yi-Fei; Huang, Zhi-Heng; Zhu, Ya-ying; Wu, Qi-Nan; Duan, Jin-Ao; Zhang, Zhu-Zhe; Wu, Chang-Jian; Ding, Qing-Qing
Graphical abstract: Highlights: 6″-O-Succcinylapigenin can be produced in large amounts by bio-transformation. It is the first time to detect the content of 6″-O-Succcinylapigenin in natto. 6″-O-Succcinylapigenin exhibits the anti-ischemic effect. 6″-O-Succcinylapigenin acts the potential bio-activities of regulating antioxidant. Abstract: 6″-O-Succinyldaidzin is a daidzin derivative in natto with little bioactivity reports. We investigated the anti-ischemic effects and underlying mechanisms of 6″-O-Succinyldaidzin in MCAO model and used MRI to measure the infarct volume, and neurological scores to evaluate the effect of the injury after occlusion for 2 h and reperfusion for 24 h on male rats. Levels of Nrf2, Keap1, HO-1, ERK were measured by immunoblots to study the underlying mechanisms of 6″-O-Succinyldaidzin activity. Further, we confirmed our results in HT-22 cells using immunofluorescence to assay for the expression of Nrf2 and Keap1. 6″-O-Succinyldaidzin reduced both infarct areas and neurological scores of MCAO rats. Levels of ERK, HO-1, and nuclear-Nrf2 were upregulated after the administration of 6″-O-Succinyldaidzin. Immunofluorescence assays indicated that Nrf2 expressed in the nucleus while Keap1 remained in the cytoplasm after treatment with 6″-O-Succinyldaidzin. Our study shows that 6″-O-Succinyldaidzin of natto elicits an anti-ischemic effect and activates Nrf2-related antioxidant.